Efficacy of Adjuvant Therapy Curcuma Longa Rhizome Extract and Moringa Oleifera Leaf Extract to Wound Healing in Leprosy Ulcer Patients - Renni Yuniati; Farmaditya Eka Putra Mundhofir; Sylvia Christiana Sugianto (Journal of Social Research, 2025)
Leprosy (Morbus Hansen) is a chronic infectious disease caused by Mycobacterium leprae, primarily affecting the peripheral nerves and leading to sensory loss and the formation of chronic ulcers. This study investigates the efficacy of Curcuma longa rhizome and Moringa oleifera leaf extracts, known for their antibacterial and anti-inflammatory properties, in promoting wound healing in leprosy-related ulcers. Utilizing a pre-post, randomized, single-blinded controlled trial design, the study was conducted at Kelet Regional Hospital, Jepara, from January to April 2024. Participants included leprosy ulcer patients with a mean disease duration of 101.5 months, predominantly male (63.6%), and largely in the 51–60 age group (39.4%). Results indicated significant improvements in PUSH (Pressure Ulcer Scale for Healing) scores from pre-test to post-test within both the intervention and control groups (p<0.001). However, intergroup analysis showed no statistically significant difference in PUSH scores between groups (pre-test p=0.669; post-test p=0.198). These findings suggest that while C. longa and M. oleifera extracts have promising therapeutic potential in enhancing ulcer healing, their clinical efficacy may be limited by factors such as oral bioavailability. This research contributes to the limited literature on the use of plant-based adjunctive therapies in leprosy ulcer management and underscores the need for further studies with larger samples and improved delivery mechanisms to optimize clinical outcomes.